2010
DOI: 10.1016/j.cnur.2010.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Uniformed Service Nurses' Experiences with the Severe Acute Respiratory Syndrome Outbreak and Response in Taiwan

Abstract: Severe Acute Respiratory Syndrome (SARS) had an enormous effect on Taiwan's public health and the nation's economy. To prevent the spread of the epidemic, the government implemented strategies and measures for the control of the epidemic. The Ministry of National Defense also fully supported epidemic prevention by mobilizing all necessary human and material resources. Under the plan executed by the Ministry of National Defense, the SongShan Armed Forces Hospital became Taiwan's first hospital dedicated exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…Although the psychological stress of nurses has been demonstrated to be higher than that of other professions and although nursing is also a high-risk occupation for psychological disease, in the context of a large-scale epidemic of infectious diseases, more attention should be paid to the special group of TNs [ 25 27 ]. The present survey about the psychological stresses of TNs found that anxiety, pain, grief and insomnia were the most common psychological problems, which is similar to other nurse-related studies, but with different causes: (1) their colleagues may be infected, and the number of infected TNs is significantly higher than non-TNs, which leads to anxiety among the TNs; (2) TNs have not been in a closed working environment and worn protective suits for a long time, which greatly challenges their psychological and physical limits; (3) unfamiliar working modes and a lack of skill in the content of their work increase their psychological burden; (4) most TNs have difficulty accepting high mortality and helplessness in the face of the large number of severe patients; and (5) compared with non-TNs, TNs suffer from more pressure from their family, and combined with concerns about their family members, their psychological burdens are significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Although the psychological stress of nurses has been demonstrated to be higher than that of other professions and although nursing is also a high-risk occupation for psychological disease, in the context of a large-scale epidemic of infectious diseases, more attention should be paid to the special group of TNs [ 25 27 ]. The present survey about the psychological stresses of TNs found that anxiety, pain, grief and insomnia were the most common psychological problems, which is similar to other nurse-related studies, but with different causes: (1) their colleagues may be infected, and the number of infected TNs is significantly higher than non-TNs, which leads to anxiety among the TNs; (2) TNs have not been in a closed working environment and worn protective suits for a long time, which greatly challenges their psychological and physical limits; (3) unfamiliar working modes and a lack of skill in the content of their work increase their psychological burden; (4) most TNs have difficulty accepting high mortality and helplessness in the face of the large number of severe patients; and (5) compared with non-TNs, TNs suffer from more pressure from their family, and combined with concerns about their family members, their psychological burdens are significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected using 7 focus group interviews and 3 individual in‐depth interviews from August to December 2015 until the data were saturated. Focus group questions were developed based on a literature review (Chou et al, ; Corley et al, ). Each focus group was comprised of 2 to 5 participants.…”
Section: Methodsmentioning
confidence: 99%
“…Along with high risk of being infected, studies reported that health care personnel experienced occupational risks, distress, and the fear of contacting and transmitting the disease during epidemics of H1N1, severe acute respiratory syndrome (SARS), and Ebola virus (Bukhari et al, 2016;Chou et al, 2010;Corley, Hammond, & Fraser, 2010;Koh, Hegney, & Drury, 2012;Speroni, Seibert, & Mallinson, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because an infected HCP is a potential vehicle for virus dissemination, research suggests that reducing the risk of infection amongst HCPs is essential [ 8 ]. Spread of virus has been reported during the Ebola outbreak resulting in a compromised healthcare system [ 9 ] as well as during the Severe Acute Respiratory Syndrome (SARS) [ 10 ] and the Middle East Respiratory Syndrome (MERS) epidemics [ 11 ]. Experiences from these previous outbreaks highlight fear among HCPs in transmitting the disease and the importance of screening for the virus.…”
Section: Introductionmentioning
confidence: 99%